PENYUSUNAN PERENCANAAN PENGEMBANGAN PEGAWAI DILINGKUNGAN PEMERINTAH KOTA SURAKARTA - Endang Tri Wahyuni (JI@P, 2018)
Wahyuni, 2018. “Preparation Of Employee Development PlanningGovernment Surakarta City“. Slamet Riyadi Surakarta University. Theses.Unpublished.The purpose of this study is to describe and analyze human resourcedevelopment planning ASN (Civil State Apparatus) in order to improve theprofessionalism of the Government apparatus resources City of Surakarta inaccordance with competency needs of the Office.The type of research used the qualitative analysis, the unit is organizations,namely the civil State Apparatus. Yangdigunakan data sources the primarydata and secondary data, do data collection techniques of observation andinterviews, data analysis Techniques in the study: 1 data Reduction) 2) 3 dataRendering) the withdrawal of the conclusion. Results of the study PlanningPengembangnan ASN there are still gaps in aspects of competence by 20%;On the aspect of compensation there is value gap amounted to 0.76, thehighest gap in the Echelon IV of 0.65 on Echelon III of 0.11, it takes the effortof reducing the gap on Echelon Echelon IV and III by giving a salary based onthe performance of the employee in order that the can be fulfilled the elementsof Justice for the performance of employees; On the aspect of performance,employee performance target values (SKP) highest on the/ruang main Builderand the Builder level I. This reflects that yet the existence of a balancebetween the level SKP value/space. To work behavior employees have metthe standards of good behavior, so planning on aspects of this work is thebehavior maintains the behavior in order to awake with good and consistentover time; On the discipline, the value of the main young Builder/space of91.20, builders of the level I of 91.40, for the Builder of 85.35/space, to thestylist/space level I of 86.81, to the stylist/space of 85.48, for the youngstylist/space level I of 83.56, to the regulator level I/space of 85.33, for theyoung Manager/space level I of 87, and for the young Manager ofspace/81.36.Key Words: Competence, Performance, Compensation, Discipline